PERBANDINGAN KEPUASAN PASIEN TERHADAP PELAYANAN KEBIDANAN PADA PESERTA BPJS DAN NON BPJS - Yosi Arum Ariningtyas (ITKES Wiyata Husada Samarinda, 2019)
All patients always expected qualified services to get their satisfaction. And all health service unit must give same services either to BPJS or non BPJS patients. This research was to know the patients’ satisfaction differences towards midwifery services of BPJS (Social Security Administrator) patients and non-BPJS patients Postpartum Room of General Hospital in Kediri. The design of this research was observational analytics by using cross-sectional methods. The population was finite, which meant it was still countable. 70 respondents were taken as samples by purposive sampling technique. The independent variables were the patients’ BPJS membership and non-BPJS, and the dependent variables were the patients’ satisfaction. The data was obtained from questionnaires and analyzed with Mann Whitney Test. The research showed that most BPJS patients, 24 respondents (77.4%) were satisfied of midwifery services, 37 non-BPJS patients (94.9%) were satisfied of midwifery services of totally 39 respondents, and there were no satisfaction level differences of BPJS and non-BPJS patients towards midwifery services in Postpartum Room of General Hospital in Kediri (p = 0.548 > 0.05 then Ho accepted).